Successful pregnancy outcome in grade IV lupus nephritis and secondary antiphospholipid antibody syndrome with recurrent pregnancy failures - challenging achievement of motherhood - Reddy, Kaliki Hymavathi; Kumar, Kolla Praveen; Tadisetti, Surekha; Pusarla, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disease that occurs predominantly in women of childbearing age. The risk of complications and adverse fetal outcomes in pregnant women with lupus is high viz., increased risks of preterm birth, hypertensive diseases of pregnancy and lupus flares both during pregnancy and in the postpartum period. An additional association with Antiphospholipid antibody (APLA) syndrome is expected to multiply the pregnancy complications. Though improved understanding of the disease nature and greater number of therapeutic options in the treatment of SLE, made the medical community regard these patients with less trepidation, the risk of significant morbidity to both the mother and the fetus still exist. We report an interesting case of grade IV Lupus nephritis (LN) with secondary APLA syndrome and h/o recurrent pregnancy failures for twenty times but had a successful pregnancy and delivery in the 21st attempt though pregnancy was absolutely contraindicated in view of her medical illness. Many complications were encountered during her pregnancy which could be successfully tackled and a live male baby was delivered by Caesarean section.